Grade G2 Rectal Neuroendocrine Tumor Is Much More Invasive Compared With G1 Tumor - Li, Yi-Wei; He, Yi-Ping; Liu, Fang-Qi; Peng, Jun-Jie; Cai, San-Jun; Xu, Ye; Wang, Ming-He (Frontiers in Oncology, 2021)
Background: To compare clinicopathologic feature of rectal neuroendocrine tumor (NET) grade G1 with G2 NET. Methods: 601 cases of rectal G1 and G2 NETs diagnosed in our center were analyzed. Results: Of 601 cases of rectal NET, 515 cases were with grade G1 and 86 cases were with grade G2. Median tumor size was 0.7 cm. Compared with G1 NET, G2 tumors were with significantly larger tumor size (0.8 vs 2.2 cm, p < 0.001), less percentages of patients with tumors confined to submucosa (92.6% vs 42.8%, p < 0.001), more frequent presence of microvascular invasion (MVI) (3.6% vs 16.9%, p < 0.001) or peri-neural invasion (PNI) (2.0% vs 24.1%, p < 0.001). Incidence of lymph node and distant metastasis was 5.2% and 2.1% infor G1 NET compared with 44.2% and 31.4% infor G2 tumor, respectively (p < 0.001). For tumors sized 1-2 cm and confined to submucosa, incidence of lymph node metastasis was 6.1% for G1 NET compared with 21.1% for G2 NET. Status of MVI/PNI was predictive of lymph node metastasis for G2 tumor rather than G1 NET in this subgroup. Conclusions: Rectal G2 NET was much more invasive with significantly elevated prevalence of lymph node metastasis compared with G1 tumor.